2020
DOI: 10.4028/www.scientific.net/jnanor.63.98
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Optimization of Magneto Rheological Abrasive Flow Nano Finishing Process on AISI Stainless Steel 316L

Abstract: In this experimental work, Magneto rheological abrasive flow nano finishing processes were conducted on AISI Stainless steel 316L work pieces that are widely used in medical implants. The focus of the present study is to assess the effect of input variables namely the volume percentage of iron (Fe) particles, silicon carbide (SiC) abrasive particles in the Magneto rheological abrasive fluid and number of cycles on the final surface roughness at nano level as well as the material removal rate. The volume % of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The material removal rate shows a positive linear dependence on shear stress according to the research of Miao and other scholars [34]. The material removal rate also seems to have a positive effect on the machined surface roughness [35,36]. Based on the comparison between wall shear stress and experiment results, this paper gives the comparative relationship between the surface roughness of the workpiece and the wall shear stress after SLTPMF machining.…”
Section: Simulation Results Analysismentioning
confidence: 76%
“…The material removal rate shows a positive linear dependence on shear stress according to the research of Miao and other scholars [34]. The material removal rate also seems to have a positive effect on the machined surface roughness [35,36]. Based on the comparison between wall shear stress and experiment results, this paper gives the comparative relationship between the surface roughness of the workpiece and the wall shear stress after SLTPMF machining.…”
Section: Simulation Results Analysismentioning
confidence: 76%
“…To conduct this measure, hearing-naïve participants were seated in separate audio-recording rooms and asked to use a telephone interactive verbal communication environment before rating the best voice using a five-factor scale. [17] In the initial phase of the current study each participant was observed from the residence during three conversations at home with their key worker.…”
Section: Conversation Qualitymentioning
confidence: 99%
“…Energy-green purposeful Flight Time Combs and is provided by way of others. Flying from side to side like agriculture in popular used in applications [4] popular for wing UAVs Coverage course planning Technique. To reduce the wind Explores, but this Type movement interested Considering the parts I nefficient with irregular shape Creating paths.…”
Section: Path Planningmentioning
confidence: 99%